Safety of an allogeneic, human, umbilical cord blood-derived mesenchymal stem cells-4% hyaluronate composite for cartilage repair in the knee - Brian J. Cole; Joshua T. Kaiser, BS; Kyle R. Wagner, BS; Andreas H. Gomoll (Elsevier, 2022)
Introduction: Knee osteoarthritis treatments that functionally restore diseased/damaged cartilage are limited. Objective: To evaluate the safety and effectiveness of allogeneic, human, umbilical cord blood-derived mesenchymal stem cells (hUCB-MSCs) + 4% hyaluronate composite for knee cartilage defects. Methods: In a 24-month, open-label, non-randomized phase 1/2a study, adults ≥18 years with single, full-thickness, ICRS grade 3 to 4 knee cartilage defects were recruited sequentially based on initial defect size (Dose A: 2-5 cm2; Dose B: >5 cm2). The hUCB-MSCs composite (0.25 × 107 cells/cm2) was surgically implanted into the defects. Safety (adverse events [AEs] and dose-limiting toxicities) was the primary objective, and efficacy was secondary. Results: Twelve patients (mean 38 years; 83% male; BMI 27.6 kg/m2) completed the study. All patients reported ≥1 treatment-emergent AE (TEAE): 42 with Dose A (n = 6); 27 with Dose B (n = 6); most common were decreased range of motion (100%) and arthralgia (92%). Seven patients (58%) had 10 treatment-related TEAEs. No discontinuations due to TEAEs, serious AEs, or deaths were reported. There were no dose-limiting toxicities; maximum tolerated dose was established as 2.0 × 107 cells. The IKDC score and other knee function and pain scores significantly improved from baseline to months 12 and 24. Clinically significant abnormal MRI findings declined from 91.7% (n = 11) at baseline to 16.7% (n = 2) at month 24. Conclusion: hUCB-MSCs + 4% hyaluronate composite implantation appears to be safe over 24 months in US patients with ICRS grade 3 to 4 knee cartilage defects, with improvements in function, pain, and cartilage repair evidence.